Acceptability and Organoleptic of Moringa Leaf (Moringa oleifera) Boba as Antioxidant-Rich Functional Beverages - Risty Fadella; Galuh Sitatorik; Arya Ulilalbab; Djembor Sugeng Walujo (Ficco Public Health Journal, 2025)
Background: Moringa oleifera, known as the “miracle tree,” is rich in antioxidants and nutrients, making it a potential ingredient in the development of functional beverages by utilizing local foods. This study aims to evaluate the acceptability and organoleptic characteristics of Moringa-based boba as an antioxidant-rich functional beverage. Method:  This study used an experimental design with a quasi-experimental approach and involved 30 semi-trained panelists. Sensory evaluation was conducted on four organoleptic parameters: color, aroma, texture, and flavor. Data analyzed using the friedman test, if significant differences (p < 0,05) were found analysis further with wilcoxon test. Results: The results showed that Moringa-based boba received positive organoleptic ratings, especially in terms of texture and color, with an average acceptance score above 3.5 on a 5-point scale. The highest percentage of acceptance for all parameters was found in P0, with details of the percentage being 98% for color, 89% for aroma, 68% for texture, and 80% for flavor. The p-value of the color parameter is 0.180, indicating that this parameter is not statistically significant. The p-value of the aroma parameter is p = 0.042, indicating that the difference in aroma between treatments is statistically significant, so that moringa leaf concentration affects the acceptance of boba aroma by panelists. In the texture parameter, the p value is p = 0.027, which means the parameter value is significant. Meanwhile, in the flavor parameter, the p value is p = 0.027, which means that the flavor parameter is significant. Conclusion: M It is necessary to formulate the product by adding ingredients containing natural sweeteners to reduce the unpleasant taste of the addition of moringa leaves while producing a softer texture.